Bitter rice - Chase, Graham (Film Australia, 1989)
An interview with Dante Buscayno by Film Australia when he was released from prison in 1986. How he organized the NPA in Tarlac and how he started a livelihood cooperative project among farmers, its advantages and disadvantages were some of the questions answered.